ANALYSIS OF THE INFLUENCE OF PHYSICAL EXERCISE ON THE PHYSICAL FITNESS OF GRADE 8 STUDENTS AT SMP NEGERI 2 KUTACANE - Ayunita Rahayu; Orbit Irwansyah; Fakhrur Rizal (RADJA PUBLIKA, 2025)
This study aims to evaluate the impact of a structured physical exercise program on the physical fitness of eighth-grade students at SMP Negeri 2 Kutacane. Employing an experimental design, a total of 20 students were randomly assigned to two groups: an experimental group that underwent a specifically designed 4-week physical training regimen and a control group that participated only in the standard, regular school sports activities. Physical fitness was quantitatively measured through a battery of standardized tests assessing various components, including the 60-meter sprint for speed, pull-ups for upper body muscular endurance, sit-ups for abdominal endurance, skipping for agility and coordination, and the vertical jump for lower body explosive power. Data collection occurred in two phases: a pre-test before the intervention and a post-test following the 4-week period. The collected data were subjected to statistical analysis, commencing with tests for normality (Shapiro-Wilk) and homogeneity (Levene's test) to validate the assumptions for parametric testing. Subsequently, a paired t-test was employed to compare the pre-test and post-test results within each group. The findings reveal a statistically significant improvement across all measured aspects of physical fitness in the experimental group, while the control group showed minimal changes. These results robustly demonstrate the profound effectiveness of a structured, consistent physical exercise program in enhancing the overall physical fitness of junior high school students. The study concludes that such programs are crucial and should be integrated into the standard physical education curriculum to foster better health and physical development among adolescents.